Morphology THE ANALYSIS OF BOUND MORPHEME ON POPULAR SONG LYRICS “BELIEVER” BY IMAGINE DRAGONS. - Aditya, Ahmad Fatir (UNMUH BABEL PRESS, 2024)
The purpose of this research is to know, find, and also learn the morpheme and bound morpheme of a song lyric Believer by Imagine Dragons. The research uses a qualitative method counting the bound morphemes using numerical data and table as the result of the research. Using other research such as William Shakespeare poetries to compare the research gap between the song lyric Believer by Imagine Dragon bound morpheme and the bound morpheme in the William Shakespeare poetries research. We found the exact percentages of each research. Imagine Dragon uses lots of bound morpheme in their lyrics while William Shakespeare poetries uses lots of free Morpheme in his works. This journal article related to linguistics of english mainly about morphologies and bound morphemes as an object purpose of the research. Suffix and Prefix are also a part of this research because of bound morphemes that cannot stand alone.